ОСОБЕННОСТИ ВЛИЯНИЯ РЫНКА НЕДВИЖИМОСТИ НА ЭКОНОМИКУ СТРАНЫ И ЕЕ РЕГУЛИРОВАНИЕ (Лучшие интеллектуальные исследования, 2025)
Аннотация: Данное исследование посвящено комплексному анализу влияния рынка недвижимости на экономику Узбекистана и совершенствованию механизмов его государственного регулирования. В работе систематизированы теоретические подходы к изучению роли рынка недвижимости в экономической системе, проанализированы основные каналы его влияния на макроэкономические показатели.Annotation: This study is devoted to a comprehensive analysis of the impact of the real estate market on the economy of Uzbekistan and improving the mechanisms of its state regulation. The paper systematizes theoretical approaches to the study of the role of the real estate market in the economic system, analyzes the main channels of its influence on macroeconomic indicators.Keywords: real estate market, government regulation, economic development, housing construction, mortgage lending, affordable housing, Uzbekistan.